217k views
1 vote
3(x+2) = 2(2x+7) — solve for x and please explain

User Agc
by
5.0k points

2 Answers

5 votes

Answer:

8

Explanation:

3(x+2) = 2(x+7)

3x + 6 = 2x + 14

3x - 2x = 14 - 6

x = 8

1 vote

3(x+2) = 2(2x+7)

3x + 6 = 4x + 14 (On the left side we distribute 3 through parenthesis and on the right side we do the same with 2)

3x - 4x = 14 - 6 (Here we move 4x from the right to the left side and it changes its sign. We do the same with 6)

-x = 8

x = - 8

User Batfastad
by
4.9k points